Deep-sea observations at hydrocarbon drilling locations: Contributions from the SERPENT Project after 120 field visits. (March 2017) - Gates, Andrew R.; Benfield, Mark C.; Booth, David J.; Fowler, Ashley M.; Skropeta, Danielle; Jones, Daniel O.B.
Abstract: The SERPENT Project has been running for over ten years. In this time scientists from universities and research institutions have made more than 120 visits to oil rigs, drill ships and survey vessels operated by 16 oil companies, in order to work with the industry's Remotely Operated Vehicles (ROV). Visits have taken place in Europe, North and South America, Africa and Australasia at water depths from 100 m to nearly 3000 m. The project has directly produced >40 peer reviewed publications and data from the project's >2600 entry online image and video archive have been used in many others. The aim of this paper is to highlight examples of how valuable data can be obtained through collaboration with hydrocarbon exploration and production companies to use existing industry infrastructure to increase scientific discovery in unexplored areas and augment environmental monitoring of industrial activity. The large number of industry ROVs operating globally increases chance encounters with large, enigmatic marine organisms. SERPENT video observations include the deepest known records of species previously considered epipelagic such as scalloped hammerhead ( Sphyrna lewini ) and southern sunfish ( Mola ramsayi ) and the first in situ observations of pelagic species such as oarfish ( Regalecus glesne ). Such observations enable improvements to distribution records and description of behaviour of poorly understood species. Specimen collection has been used for taxonomic descriptions, functional studies and natural products chemistry research. Anthropogenic effects been assessed at the local scale using in situ observations and sample collection at the time of drilling operations and subsequent visits have enabled study of recovery from drilling. Future challenges to be addressed using the SERPENT approach include ensuring unique faunal observations by industry ROV operators are reported, further study of recovery from deep-water drilling activity and to carry out in situ studies to improve the understanding of potential future decommissioning of obsolete hydrocarbon infrastructure.